1985
DOI: 10.1002/aja.1001730204
|View full text |Cite
|
Sign up to set email alerts
|

Graded morphogenetic patterns during the development of the extraembryonic blood system and coelom of the chick blastoderm: A scanning electron microscope and light microscope study

Abstract: This scanning electron- and light-microscopic study traces the morphogenesis of the yolk-sac vascular system and extraembryonic coelom in the chick blastoderm. The fate of the mesodermal cells in both the area opaca vasculosa (AOV) and the area pellucida (AP) is followed, and the cellular patterning in these two areas is compared. We describe new details of the formation of coelom lining in the AOV, and new observations of the tendency of the intravascular blood island cells of the AOV to become flattened and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…A similar model for the early separation of cells contributing to the BC/EC lineage and cells contributing to the extraembryonic coelomic linings was proposed by Sabin (Sabin, 1920), although the SMC nature of coelomic lining cells was not clearly mentioned in that report. The general anatomical organization, proposed in this work, of the extraembryonic mesoderm in the chick embryo, is also supported by ultrastructural studies (Kessel and Fabian, 1985;Murphy and Carlson, 1978).…”
Section: Research Articlesupporting
confidence: 54%
See 1 more Smart Citation
“…A similar model for the early separation of cells contributing to the BC/EC lineage and cells contributing to the extraembryonic coelomic linings was proposed by Sabin (Sabin, 1920), although the SMC nature of coelomic lining cells was not clearly mentioned in that report. The general anatomical organization, proposed in this work, of the extraembryonic mesoderm in the chick embryo, is also supported by ultrastructural studies (Kessel and Fabian, 1985;Murphy and Carlson, 1978).…”
Section: Research Articlesupporting
confidence: 54%
“…1A). The BC/EC progenitors aggregate to form blood islands within the extraembryonic splanchnic mesoderm, which contains in addition vascular SMCs (Kessel and Fabian, 1985;Murphy and Carlson, 1978;Sabin, 1920). The extraembryonic somatic mesoderm gives rise to mesothelial cells lining the ectoderm, from which the amnionic and chorionic membranes are derived (Adamstone, 1948;Oppenheim, 1966;Pierce, 1933;Romanoff, 1960;Wu et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The splanchnic wall of the extraembryonic coelom is the source of cells for the vascular smooth muscle layer during vasculogenesis, and after formation of the vascular network, vascular smooth muscle layer is in direct contact with the extraembryonic coelomic cavity. This general organization of somatopleural and splanchnopleural tissues in the yolk sac is supported by ultrastructure studies (Kessel and Fabian, 1985;Murphy and Carlson, 1978).…”
Section: Extraembryonic Mesoderm and Ventral Mesodermmentioning
confidence: 53%
“…However, the first blood vessels within the embryo always form in mesoderm that is in close proximity to endoderm (Mato et al, 1964;Wilt, 1965;Gonzalez-Crussi, 1971;Mobbs and McMillan, 1979;Meier, 1980;Kessel and Fabian, 1985;Pardanaud et al, 1989). Furthermore, we have recently demonstrated that a signal originating from the endoderm is essential for the assembly of angioblasts into tubes (Vokes and Krieg, 2002a).…”
Section: Introductionmentioning
confidence: 99%